Model penelitian fiqh : paradigma penelitian fiqh & fiqh penelitian - Bisri, Hasan, 1946- (Jakarta : Kencana, 2003)
Studies and research methods in Islamic law in Indonesia
Daftar pustaka (j. 1, p. [391]-414)
Keywords: Islamic law -- Indonesia; Islamic law -- Interpretation and construction